Playing the first or the second bounce in wheelchair tennis - Sánchez-Pay, A.; Sanz-Rivas, D.; Torres-Luque, G. (Coaching and Sport Science Review, 2018)
The objective of this article is to analyse the influence of the use of the bounce on the differences between the winner and the loser of a set during a tournament in wheelchair tennis (WT). A total of 16 international matches were recorded and analysed. The type of stroke and the number of bounces before hitting the ball were also studied. The results showed that WT players usually hit the ball after the first bounce (80.95%) and 97.19% of returns are hit after the first bounce. The second bounce is significantly used by the winners of the set. Furthermore, the use of the second bounce by WT players reduces the number of errors and increases the number of winners when compared with hitting the ball off the first bounce.